Antibody-Mediated Rejection With and Without HLA Donor-Specific Antibodies in Kidney-Transplantation. (July 2018) - Crespo, Marta; Redondo, Dolores; Butler, Carrie; Gimeno, Javier; Garcia, Carme; Perez, Maria Jose; Burballa, Carla; Mir, Marisa; Faura, Anna; Valenzuela, Nicole M; Reed, Elaine F; Julio, Pascual
Abstract : Background: Correlation between antibody-mediated damage (AMR) and HLA donor-specific antibodies (DSA) is strong but imperfect in kidney transplant (KT) recipients. We reviewed histopathology and HLA DSA in AMR patients and compared them with those with only interstitial fibrosis and tubular atrophy (IFTA) or no abnormalities. Methods: Retrospective assessment of patients with biopsies (Banff'13) and serum samples (pre- and postransplant) tested for HLA antibodies. Results: A total of 118 patients were studied. The diagnoses were normal biopsy (n=16), AMR (n=53) and IFTA (n=49). Death-censored graft survival was worse in patients with AMR than with IFTA or normal biopsies. Pre-transplant DSA were more frequent in AMR cases than IFTA or normal ones (46.3%, 20.5 and 6.3%, p=0.003). Differences were mostly due to pre-transplant DSA combined I&II (22 vs 2.3 and 0%, p=0.004) but not to isolated DSA class I or II. At biopsy, 75.5% AMR patients had HLA DSA (7.5% class I, 54.7% II and 13.2% combined I&II), but also 14.6% of IFTA and 6.3% of normals. Twelve AMR patients (22.6%) had no DSA pre-transplant or peri-biopsy. AMR patients with and without DSA were similar at baseline, except that more DSA+AMR patients were sensitized pretransplant and less well DR-matched, with no differences in graft function or immunosuppression. Patients with AMR with or without DSA showed similar microvascular inflammation and chronic changes. Conclusions: 20% of patients with AMR do not show circulating HLA DSA. These patients are more frequently HLA unsensitized pre-transplant, without other differences at transplantation, in their biopsies or at follow-up. Figure. No caption available. Figure. No caption available.